Joint Pricing and Inventory Control for Non-instantaneous Deteriorating Items with Stochastic Demand - Somayeh Najafi Ghobadi; Isa Nakhai Kamalabadi; Mohammad Aghdasi (International Journal of Supply Chain Management, 2012)
In recent years inventory and pricing of deteriorating items has gained an enormous attention by many researchers. In this study, an inventory system for non-instantaneous deteriorating items with stochastic demand is modeled. This model has the assumptions that shortages are allowed and backlogging rate is variable where the last one is defined as a function of waiting time for the next replenishment. The objective is to maximize the total profit per unit time by finding the optimal selling price and replenishment schedule simultaneously. The concavity of the function is proved with a unique optimal solution. Thereby we provide an algorithm for finding the optimal solution. Finally, the authors present a numerical example to illustrate the theoretical results. A sensitivity analysis for the optimal solution with respect to major parameters is also carried out.